Black Phosphorus: Ambient Protection of Few‐Layer Black Phosphorus via Sequestration of Reactive Oxygen Species (Adv. Mater. 27/2017). Issue 27 (July 2017) - Walia, Sumeet; Balendhran, Sivacarendran; Ahmed, Taimur; Singh, Mandeep; El‐Badawi, Christopher; Brennan, Mathew D.; Weerathunge, Pabudi; Karim, Md. Nurul; Rahman, Fahmida; Rassell, Andrea; Duckworth, Jonathan; Ramanathan, Rajesh; et al.
Abstract : Few‐layer black phosphorous (BP) has emerged as a promising candidate for next‐generation nanophotonic and nanoelectronic devices. However, rapid ambient degradation of mechanically‐exfoliated BP poses challenges in its practical use in devices. In article number1700152, Sumeet Walia, Vipul Bansal, and co‐workers describe an approach that allows the material to remain stable without requiring its isolation from the ambient environment, opening opportunities to implement BP and other environmentally‐sensitive two‐dimensional (2D) materials for electronic applications.